Nutrition status of children in Nepal: Analysis from the findings of Nepal Demographic Health Survey 2016 - Pokharel, Ridesh; Pokharel, Bibhor; Bhusal, Rajan; Chapagain, Deepika (Grande Medical Journal, 2019)
Introduction: Nutrition is simply the process of intake of food which is required according to the body need. A well balanced food with regular physical activity is a foundation for a good health. Some effects in health such as reduced immunity, increased susceptibility to disease, poor physical and mental development and reduction in productive capacity can be seen as a result of poor nutrition. The indicators of nutrition are stunting, wasting, underweight and overweight among the children. Methods: The 2016 Nepal Demographic Health Survey (NDHS) measured the height and weight of eligible children under age 5 in sample households. Weight measurements were taken from lightweight SECA infant scales with a digital display (model no. SECA 878U), designed and supplied by the United Nations Children’s Fund (UNICEF). Height was measured with a measuring board (Shorr Boards®). Recumbent length was measured for children younger than age 24 months, and standing height was measured for older children. Results: Overall, 36% of children under age 5 were stunted, with 12% being severely stunted (too short for their age); 10% were wasted, with 2% severely wasted (too thin for their height); and 27% were underweight, with 5% severely underweight (too thin for their age), while around 1% of the children were overweight (heavy for their height). Conclusion: The different indicators of nutritional status among children such as stunting, wasting and underweight are decreasing. The national program and effective contribution from several non-governmental agencies is the main reason for the improvement in nutritious status.